Influence of the heavy-atom effect on singlet fission: a study of platinum-bridged pentacene dimers. Issue 48 (30th October 2019) - Basel, Bettina S.; Young, Ryan M.; Krzyaniak, Matthew D.; Papadopoulos, Ilias; Hetzer, Constantin; Gao, Yueze; La Porte, Nathan T.; Phelan, Brian T.; Clark, Timothy; Tykwinski, Rik R.; Wasielewski, Michael R.; Guldi, Dirk M.
Abstract : Two platinum-bridged pentacene dimers undergo efficient singlet fission to form a correlated triplet pair (T1 T1 ). The internal heavy-atom effect of the platinum allows for 1 (T1 T1 )– 3 (T1 T1 ) mixing leading to the formation of mainly (T1 S0 ). Abstract : The process of singlet fission (SF) produces two triplet excited states (T1 + T1 ) from one singlet excited exciton (S1 ) and a molecule in its ground state (S0 ). It, thus, possesses the potential to boost the solar cell efficiency above the thermodynamic Shockley–Queisser limit of 33%. A key intermediate in the SF mechanism is the singlet correlated triplet pair state 1 (T1 T1 ). This state is of great relevance, as its formation is spin-allowed and, therefore, very fast and efficient. Three fundamentally different pathways to formation of 1 (T1 T1 ) have been documented so far. The factors that influence which mechanism is associated with which chromophore, however, remain largely unknown. In order to harvest both triplet excitons independently, a decorrelation of the correlated triplet pair state to two individual triplets is required. This second step of the SF process implies a change in the total spin quantum number. In the case of a dimer, this is usually only possible if the coupling between the two pentacenes is sufficiently weak. In this study, we present two platinum-bridged pentacene dimers in which the pentacenes are coupled strongly, so that spin-decorrelation yielding (T1 + T1 ) was initially expected to be outcompeted by triplet–triplet annihilation (TTA) to the ground state. Both platinum-bridged pentacene dimers undergo quantitative formation of the (T1 T1 ) state on a picosecond timescale that is unaffected by the internal heavy-atom effect of the platinum. Instead of TTA of (T1 T1 ) to the ground state, the internal heavy-atom effect allows for 1 (T1 T1 )– 3 (T1 T1 ) and 1 (T1 T1 )– 5 (T1 T1 ) mixing and, thus, triggers subsequent TTA to the (T1 S0 ) state and minor formation of (T1 + T1 ). A combination of transient absorption and transient IR spectroscopy is applied to investigate the mechanism of the (T1 T1 ) formation in both dimers. Using a combination of experiment and quantum chemical calculations, we are able to observe a transition from the CT-mediated to the direct SF mechanism and identify relevant factors that influence the mechanism that dominates SF in pentacene. Moreover, a combination of time-resolved optical and electron paramagnetic resonance spectroscopic data allows us to develop a kinetic model that describes the effect of enhanced spin–orbit couplings on the correlated triplet pair state.